The effect of dehydroepiandrosterone (DHEA) supplementation on estradiol levels in women: A dose-response and meta-analysis of randomized clinical trials - Zhu, Yan; Qiu, Lei; Jiang, Fangfang; Găman, Mihnea-Alexandru; Abudoraehem, Ohoud Saleh; Okunade, Kehinde S.; Zhang, Ming (Steroids, 2021)
•DHEA supplementation was associated with increase in estradiol in women.•Estradiol levels increased significantly with DHEA dosages of 50 mg/day.•Estradiol was significantly greater increased in subjects aged ≥60 years old. Estradiol, an estrogen steroid hormone, serves as the dominant female hormone and its levels fluctuate during lifetime. In women, after the menopause, all estrogens and almost all androgens are locally developed in the peripheral tissues from dehydroepiandrosterone (DHEA). However, the effect of DHEA supplementation on estradiol levels in women is unclear as previously published data has resulted in conflicting findings. Thus, we conducted the present dose–response meta-analysis of randomized controlled trials (RCTs) evaluating the influence of DHEA on estradiol concentrations in women. The PubMed/Medline, Embase, Web of Science and Scopus databases were systematically searched for articles published on this topic until May 10, 2021. No time or language restrictions were applied. The data were expressed as weighted mean differences (WMDs) and 95% confidence intervals (CI), and a P-value of less than 0.05 was considered to be statistically significant. The pooled results were obtained using the generic inverse of variance method with a random effects model. A total of 21 arms, including 1223 participants (case = 610, and control = 613), reported estradiol concentrations as an outcome measure. The overall results demonstrated that estradiol significantly increased following the administration of DHEA (WMD: 7.02 pg/mL, 95% CI: 5.43, 8.62, P = 0.000). The stratified analyses revealed that the elevation of estradiol concentrations was more pronounced in subjects aged ≥60 years old (WMD: 8.56 pg/mL, 95% CI: 6.97, 10.16, I2 = 94%) and in those receiving DHEA supplements for ≥26 weeks (WMD: 7.30 pg/mL, 95% CI: 6.28, 8.32, I2 = 61%). Moreover, estradiol levels increased significantly with DHEA dosages of 50 mg/day (WMD: 7.75 pg/mL, 95% CI: 9.12, 9.39, I2 = 94%) and when DHEA was prescribed to postmenopausal women (WMD: 7.61 pg/mL, 95% CI: 5.97, 9.24, I2 = 93%). This meta-analysis has provided a comprehensive overview of the effects of DHEA administration on circulating estradiol levels, far beyond the available evidence from different RCTs. Subsequent subgroup analyses revealed that postmenopausal women, females aged 60 years and above, those on DHEA dosages of 50 mg/day and those receiving DHEA for ≥26 weeks registered a more pronounced elevation of the circulating estradiol levels.